THE CREATION OF A DANCE FROM THE BEHAVIOR OF “HUNGER FOR SPOTLIGHT” - Soontornsima, Kanokchom; Charassri, Naraphong (Fine Arts Journal: Srinakharinwirot University, 2024)
This research article is part of a thesis entitled The Creation of Dance Art from the Behavior of “Hunger for Spotlight.” The objective is to create a creative dance performance utilizing the concepts of modern dance and postmodern dance. The researchers used qualitative research methods and creative research methods including interviews, information media, the researcher’s experience, and artist benchmarks. The researcher emphasized behaviors of “Hunger for Spotlight.” Then the researcher analyzed the collected data to identify patterns and concepts emerged from the creative process of dance creation. The results showed that the creation of dance from the behaviors of “Hunger for Spotlight.” has a form of creative dance encompassing 8 elements: 1) Performance Script; inspiration from past and present events in the society of the desire for identity, both negatively and positively. The researcher therefore divided into 3 acts, consisting of Act 1: Beginning of “Hunger for Spotlight”, Act 2: Receiving the Spotlight, Act 3: Preserving the Spotlight, to demonstrate different aspects of “Hunger for Spotlight” behavior. 2) Dance Style; the researcher uses the traditional Thai dancing style and everyday movement, improvisation according to the principles of postmodern dance Including designing traditional Thai dances to present. 3) Casting; nine performers were selected based on their Thai dance skills and versatility, including five male and four female dancers. 4) Props; performance equipment were chosen to complement the script, such as tripods, mobile phones, rice plates, and bags. 5) Sound; the music for the performance included traditional Thai music, interview sounds, and newly composed songs. 6) Costumes; dress included both the traditional Thai dance style and contemporary outfits that matched the script. 7) The performance space; the performance took place in the theatre. 8) Lighting; the use of light conveys meaning and reflects the mood of the performance both in the past and present contexts. In addition, it was found that there were six concepts gained after the creation of dramatic art from “Hunger for Spotlight” behavior which are 1) the behavior of “Hunger for Spotlight”, 2) reflection on social problems, 3) creativity in dramatic art, 4) communication with audiences, 5) use of symbols in dramatic art creation, and 6) theoretical aspects of fine arts. In this regard, this research is a creative thesis in dance integrating interdisciplinary knowledge, providing insights and guidance for future studies in creative dance.